The Headmaster’s Management Strategy to Handle the Teachers’ Work Stress at Faza Islamic Primary School Palembang - Sari, Putri Dian; Harapan, Edi; Puspita, Yenny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The aim of this research is to determine the principal's management strategy in dealing with teacher work stress. The research method using qualitative method with a descriptive approach. This research uses observation, in-depth interviews, and documentation to gather the data. Research subjects are the principal and teachers of Faza Islamic Elementary School Palembang. The results of research showed that the principal can implement three strategies in dealing with teacher work stress, so it does not interfere with teacher performance, the comfort of students, and does not hinder the school to achieve its goals. The strategies applied by the principal are 1) recognizing the symptom of teacher work stress, 2) identifying the emergence of work stress, 3) solve the problem as a result of work stress, then the principal deal with teacher work stress. This problem solving consist of three approaches, 1) through a personal approach, 2) a religious approach, 3) an official approach.